The Regulation of Foreign Workers as Technology and Knowledge Transfer - Rismawati, Eka; Jaelani, Abdul Kadir; AygÃ¼n, Karakitapoglu (Lembaga Contrarius Indonesia, 2023)
The regulation of using foreign employees as a tool for technology and knowledge transfer, roadblocks that arise while implementing technology and knowledge transfer, and government initiatives to promote the quickening of technology and knowledge transfer are all examined in this study. This study is a normative legal investigation. Legal main and secondary sources are examples of primary data. The method for gathering data was a literature review, which involved reading books, looking over rules and regulations, and looking over other relevant research findings. The findings of this study suggest that Indonesia's laws governing the employment of foreign workers have not explicitly restricted the means through which technology can be transferred through foreign workers.